Inflation and Growth of SMEs in Nigeria: A Pre and Post Fuel Subsidy Period Analysis - Chukunalu, Mgbomene; Olufemi, Awogbemi Titus; Dim, Henry Chinedu; Okoro, Esther Nkechi; Duru, Erasmus Ejike (International Journal of Economics and Financial Issues, 2025)
The focus of this research is on inflation and growth of SMEs in Nigeria: A pre and post fuel subsidy period analysis. This study set out to achieve the specific objectives of investigating the relationship between inflation rate, exchange rate, interest rate, average fuel pump price and SMEs output in Nigeria before and after fuel subsidy removal periods. The data were collected monthly from 2022M01 to 2024M12. The month of May 2023 was observed as the structural break period in the analysis. The Structural break analysis was conducted using the Chow breakpoint test and the result revealed that there was structural break in SMEs output at the specified break point (2023:M05) as a result of the inflation effect resulting from fuel subsidy removal. The Chow forecast estimates further revealed that inflation rate and fuel price exerted positive effects on SMEs output before and after fuel subsidy removal periods while exchange rate and interest rate had a significantly negative effect on SMEs output before and after fuel subsidy removal. The study concluded that inflation effect of fuel subsidy removal was not severe on SMEs in Nigeria because they have monopolistic tendencies which make them transfer the increasing cost of production on to consumers hence hedging against inflationary trends. The only strain experienced by SMEs was from exchange rate fluctuations and rise in capital acquisition (interest rate). The study recommended interest rate reduction for SMEs, foreign exchange provision for export trades and stable fuel price to ease SMEs operation in Nigeria.